Seismic Retrofit of Hospitals by Means of Hysteretic Braces: Influence on Acceleration-Sensitive Non-structural Components - Gandelli, Emanuele; Taras, Andreas; Distl, Johann; Quaglini, Virginio (Frontiers in Built Environment, 2019)
The paper illustrates an investigation on the effectiveness of dissipative bracing (DB) systems for seismic retrofit of buildings with sensitive non-structural components (NSCs) and technological content (TC), such as medical centres. The “Giovanni Paolo II” hospital, located in a high seismic prone area in Southern Italy , is chosen as case-study. The retrofit intervention with hysteretic braces is designed according to the Italian Building Code. The seismic response of the hospital building is investigated by means of nonlinear history analyses carried out in OpenSees FE code and, in order to verify the full-operation after the earthquake, the integrity of NSCs and TC is checked. The retrofit design, thanks to the stiffening and damping effects introduced by DB system, proves suitable to protect both the structural frame and “drift-sensitive” non-structural components and content even under severe earthquakes (PGA=0.45g). Nevertheless, some concerns arise about the suitability of hysteretic braces for the protection of the “acceleration-sensitive” elements of the medical complex. Indeed, during weak earthquakes (PGA=0.17g), failures of several of these components are detected which can substantially impair the operation of the hospital in the aftermath of the seismic event.